Fine Differences The Al-Alwani Muslim-Christian Lectures 2010-2017 - Jones, Richard J. (International Institute of Islamic Thought, 2020)
Reaffirming our joint spiritual journey to God, and spiritual responsibility towards humanity is the burden we all share and the antidote to bigotry, prejudice, and all those ideologies that betray mankind's sense of compassion and justice. Wholeness - despite our persisting fine differences - for society and for persons is the theme of this Muslim-Christian dialogue sustained for six years in Washington, D.C. The power of faith is the power to unite and the recognition of commonalities through the medium of communication is one path to achieve this, and one element of Iraqi legal scholar Taha Jabir al-Alwani's greater vision. In 2007 a conversation began between John W. Crossin, a priest of the Order of St. Francis de Sales seeking to open the door of the forty-year-old Washington Theological Consortium - heretofore all-Christian - and Ahmed Alwani, son of Taha Jabir al-Alwani. The younger Alwani was seeking an institutional partner for his father's project of relating Islamic scholarship to Western social sciences. • Must religious emotions and ideas fuel social conflict? • Who pays the cost of mediating conflict? • What is the right way to value human labor? • Who and what is meant by the Qur'an's reference to the "People of the Book" ? Addressing these divisive issues, Muslim and Christian thinkers in pairs dig down toward their respective ultimate convictions. Occasionally the pair concurs. Always they elucidate their fine differences.